Peran kepala dinas dalam inovasi program public health lokal di Daerah Istimewa Yogyakarta - Febria Rahmi; Yodi Mahendradata; Mubasysyir Hasanbasri (Berita Kedokteran Masyarakat (BKM), 2017)
Role of local health managers in innovating district level public health programs in Yogyakarta ProvincePurpose: The study aimed to describe the strategic decision making by the heads of the DIY health departments concerning the issue of maternal and child health and nutrition.Methods: This qualitative research was an exploratory study.Results: The district health office for Yogyakarta city in the Special Region of Yogyakarta does not have many strategic decisions to solve problems about maternal and child health and nutrition. However, the decisions are always hampered by human resources. Only the Gunung Kidul District Health Office stated that there was no political involvement in decisions by the head of the health department.Conclusions: The decisions made by heads of health department are still limited to the strategic plan and local medium term development plan (RPJMD). Not many innovations are developed to overcome the problems of maternal and child health and nutrition.